Tanques-rede de pequeno volume instalados em viveiros de piscicultura: uma alternativa para a tilapicultura na região sudeste do Brasil - Pinto, Cleide Schmidt Romeiro Mainardes (2006)
Three experiments were carried out at the Aquaculture Section of the Center for the Technological Development of Agribusiness in Pindamonhangaba, Sao Paulo, Brazil, whose objective was to test the use of low-volume cages in populated or not populated ponds, aiming for a better utilization of the flooded area, as well as to assess the productivity of tilapia strains. The experiments were brought to an end when the units from at least one treatment reached mean weight value of 500g (commercial size). The first experiment was carried out from March to July 2000 (fall/winter). Three cages populated with Thai tilapia (Oreochromis niloticus) male juveniles, and three cages populated with red tilapia Oreochromis urolepis hornorum x Oreochromis mossambicus) male juveniles, at densities of 200, 250 and 300 fish/m³ were placed in each pond. After 126 days of culture, final mean weight and mean biomass were the double for the Thai tilapia than for the red one at the studied densities. The red tilapia did not reach commercial size at any of the densities. Feed conversion ranged from 1.24 to 1.50:1 among the densities, and survival rate was over 90% for all the treatments. The studied abiotic variables, with the exception of temperature, exhibited suitable values for the culture of tilapia. The objective of the second experiment, carried out from February to April 2001 (summer/fall), was to assess the productivity of the Thai tilapia in cages (intensive culture) placed in populated (semiintensive culture) or not populated ponds. Six cages with Thai tilapia males, at densities of 200, 250 and 300 fish/m³ were placed in the two ponds (V1 and V2). V2 was also populated with 4800 free male units of the same species. After 76 days of culture, the tilapia from the cages in P1 reached mean weight higher than 500g. In V2, only the units kept at the density of 200 fish/m³ reached 500g.Apparent feed conversion was around 1.0:1 for the confined fish and 1.3:1 for the free ones; survival rate was over 90% for all the treatments. The net yield in V2 was 2.7 times higher than in V1.The third experiment, carried out between February and June 2002 (summer/fall), examined the productivity of the Thai tilapia, as well as the effect of the amount of cages on the pond carrying capacity. Two ponds (V1 and V2) were populated with 4800 Thai tilapia male units. Six cages with 250 units each were placed in V1, and twelve (also with 250 units each) were placed in V2. After 60 days, the mortality rate in V2 was 35% for the confined population and 15% for the free fish, due to a sharp decrease in the dissolved oxygen concentration, suggesting that the pond had reached its maximum carrying capacity. At the end of the experiment, after 120 days of culture, only the units from the cages placed in V1 reached commercial size.